2018
DOI: 10.1089/hum.2018.015
|View full text |Cite
|
Sign up to set email alerts
|

Severe Toxicity in Nonhuman Primates and Piglets Following High-Dose Intravenous Administration of an Adeno-Associated Virus Vector Expressing Human SMN

Abstract: Neurotropic adeno-associated virus (AAV) serotypes such as AAV9 have been demonstrated to transduce spinal alpha motor neurons when administered intravenously (i.v.) at high doses. This observation led to the recent successful application of i.v. AAV9 delivery to treat infants with spinal muscular atrophy, an inherited deficiency of the survival of motor neuron (SMN) protein characterized by selective death of lower motor neurons. To evaluate the efficiency of motor neuron transduction with an AAV9 variant (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
527
4
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(544 citation statements)
references
References 33 publications
(44 reference statements)
10
527
4
3
Order By: Relevance
“…Another example, where results from rodent studies do not translate directly to studies with large animal models, is the recent observation that high doses (2e14 GC/kg) of rAAV9 vectors can lead to severe acute toxicity in piglets and non-human primates when delivered intravenously [91,92]. In this case, and different from the trial results reported by Manno et al [59], the toxicity was likely due to an acute, innate immune response (around 5 days after vector administration).…”
Section: Lessons Learned From Ex-vivo Successmentioning
confidence: 99%
“…Another example, where results from rodent studies do not translate directly to studies with large animal models, is the recent observation that high doses (2e14 GC/kg) of rAAV9 vectors can lead to severe acute toxicity in piglets and non-human primates when delivered intravenously [91,92]. In this case, and different from the trial results reported by Manno et al [59], the toxicity was likely due to an acute, innate immune response (around 5 days after vector administration).…”
Section: Lessons Learned From Ex-vivo Successmentioning
confidence: 99%
“…For example, a recent experiment in rhesus monkeys found that the high doses of AAV that may need to be delivered intravenously for some therapies could be prohibitively toxic. 52 In three out of three primates and three out of three piglets, the investigators found that the high doses of AAV used resulted in severe toxicity, including hepatocellular necrosis and axonopathies in both the central and peripheral nervous system of the monkeys, and neuronal degeneration in the dorsal root ganglia of the piglets. In commenting on this report, Flotte et al 53 noted that the doses used in the animals with these serious outcomes are nevertheless being used in human trials that so far have not encountered dose-limiting toxicity, and that the toxicity encountered in the primates and piglets could have been due to some unidentified contaminants in the viral preparation.…”
Section: Clinical Trial Issuesmentioning
confidence: 99%
“…A second reason for caution is that the limitations of gene therapy vectors for treatments requiring distribution to the entire body, as some gene‐editing treatments might require, are still being learned and may not always be appreciated. For example, a recent experiment in rhesus monkeys found that the high doses of AAV that may need to be delivered intravenously for some therapies could be prohibitively toxic . In three out of three primates and three out of three piglets, the investigators found that the high doses of AAV used resulted in severe toxicity, including hepatocellular necrosis and axonopathies in both the central and peripheral nervous system of the monkeys, and neuronal degeneration in the dorsal root ganglia of the piglets.…”
Section: Challenge 1: Avoiding Overoptimismmentioning
confidence: 99%
“…Remarkably, this treatment triggered elevated serum aminotransferase levels in only few patients and these were attenuated by prednisolone. In contrast, a separate study employing pigs and NHPs exposed to dose‐matched AAV9 expressing the same transgene and administered similarly showed massive vector and transgene‐related toxicity, motor neuron degeneration, and even fatalities (Hinderer et al, ). The discrepancy between large animal models and clinical observations is difficult to reconcile but may highlight the inherent limitations of animal models as predictors of outcome for human studies.…”
Section: Adeno‐associated Viruses—research Tools and Gene Therapymentioning
confidence: 99%